The Counsellor — An Affective Educator - Christie, Tasso G.; Williamson, John A. (Canadian Journal of Counselling and Psychotherapy, 2012)
Today's education must be relevant, and towards this end guidance counsellors and teachers should join forces in providing students with more than the traditional familiarity in various disciplines, and the acquisition of technical skills. This paper deals with the collaboration of counsellor and teacher in this concern with the development of "whole persons." It suggests a variety of intervention strategies counsellors may use to improve classroom learning environments, and concludes with a program which exemplifies these tactics.